Formwork-free hydrophobic concrete and green low-carbon preparation method thereof

CN123003248APending Publication Date: 2026-10-30FUJIAN ACAD OF BUILDING RES CO LTD +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611184077.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

1. 脆性大与开裂风险:高密实混凝土往往伴随高脆性,在干缩应力或环境温度变化下极易产生贯穿性微裂缝

Benefits of technology

1、超低碳排放:本发明以钢渣、镍铁渣、矿渣、玻璃微粉等多源工业固废为主体胶凝材料,水泥替代率可达100%,单方混凝土固废利用率超过70%,碳排放较传统C50混凝土降低50%以上。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003248A_ABST
    Figure CN123003248A_ABST
Patent Text Reader

Abstract

The application belongs to the field of building materials and digital construction technology, and particularly relates to a formwork-free hydrophobic concrete and a green low-carbon preparation method thereof. The preparation method comprises the following steps: compounding and activating steel slag micro powder, nickel-iron slag micro powder and slag micro powder, pre-mixing and ball-milling modification of glass micro powder and silane emulsion, oxygen plasma treatment of PP-HDPE fiber, modification of rubber particles by silane coupling agent, mixing and stirring of each component in a specific order, formwork-free construction by screw pump conveying to extrusion molding equipment, and finally gradient curing to obtain the finished product. The application realizes complete replacement or ultra-low dosage of cement through multi-source solid waste synergistic gelation, and the carbon emission is reduced by more than 50% compared with traditional concrete; through alkali activation-silane synergistic waterproofing and crystallization self-healing mechanism, the impermeability grade of the concrete reaches more than P12, and the 0.2mm crack healing rate is not less than 92% after 28d; through rheological regulation, the material has good extrudability and stackability, and has good 3D printing adaptability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building materials and digital construction technology, and in particular relates to a formwork-free hydrophobic concrete and its green and low-carbon preparation method. Background Technology

[0002] In modern construction engineering, structures such as basements, tunnels, and water tanks place extremely high demands on the waterproofing performance of concrete. Traditional waterproofing methods mainly rely on laying waterproof membranes or applying waterproof mortar externally. As the requirements for the waterproofing performance of concrete in underground engineering, tunnels, and water conservancy facilities continue to increase, the external waterproofing layer is prone to aging and damage, and once local leakage occurs, moisture often flows between the waterproofing layer and the structural layer, making repairs extremely difficult.

[0003] Existing self-waterproofing concrete mainly achieves this by reducing the water-cement ratio or adding expansion agents or ordinary waterproofing agents. However, this technology has the following bottlenecks: 1. High brittleness and cracking risk: High-density concrete is often accompanied by high brittleness, and is very prone to developing penetrating microcracks under drying shrinkage stress or changes in ambient temperature.

[0004] 2. Weak interfacial adhesion: Traditional organic waterproofing components (such as ordinary polymer emulsions) often reduce the later strength of concrete.

[0005] 3. Short hydrophobicity duration: Simple surface treatment or shallow admixture cannot guarantee that concrete has long-term impermeability across the entire cross-section.

[0006] 4. High carbon emissions: The traditional silicate cement production process generates huge amounts of CO2 emissions, which contradicts the national "dual carbon" strategic goal.

[0007] 5. Outdated construction methods: Traditional pouring techniques are difficult to use for the precise construction of complex and irregular structures, and they consume a lot of formwork and rely heavily on manual labor. Summary of the Invention

[0008] The technical problem to be solved by this invention is to provide a template-free hydrophobic concrete and its green and low-carbon preparation method, which uses industrial solid waste as the main cementitious material to prepare concrete with excellent self-waterproofing performance and is compatible with 3D printing intelligent construction.

[0009] This invention is implemented as follows: This invention first provides a method for preparing formwork-free hydrophobic concrete, comprising the following steps: (1) After mixing the all-solid waste cementitious system or the low-cement cementitious system, grind it in a ball mill so that the specific surface area of ​​the mixed powder is not less than 400 m² / kg; add some silane coupling agent to the ground mixed powder, stir and mix evenly to perform surface modification; the all-solid waste cementitious system or the low-cement cementitious system includes steel slag powder, nickel iron slag powder and slag powder; (2) After premixing glass micro powder with a portion of silane emulsion, ball milling was performed to modify the glass micro powder. (3) Place the PP-HDPE blended fibers in an oxygen plasma treatment machine for 3 to 5 minutes; (4) The rubber particles are premixed with the remaining silane coupling agent to obtain modified rubber particles; (5) Dissolve the alkali activator in water, stir until completely dissolved, and let stand and cool to room temperature to obtain an alkali activator solution; (6) The remaining water, silane emulsion and polycarboxylate superplasticizer are ultrasonically emulsified and dispersed to obtain a functional component mixture; (7) Dry mix the aggregate, the composite activated micro powder obtained in step (1), the modified glass micro powder obtained in step (2) and the thixotropic agent, and then add the alkali activator solution prepared in step (5) and the functional component mixture obtained in step (6), and stir evenly. (8) Add the PP-HDPE blended fiber treated in step (3), the modified rubber particles obtained in step (4), and the cement-based penetrating crystallizing waterproofing agent evenly to the mixture obtained in step (7), and continue to stir evenly to obtain a formwork-free hydrophobic concrete mixture. (9) The concrete mixture is transported to the print head by a screw pump for extrusion molding; (10) After extrusion molding is completed, cover with film and cure.

[0010] Further, in step (1), in the all-solid waste cementing system or low-cement cementing system, ordinary silicate cement is 0-80 parts by weight, steel slag powder is 80-150 parts by weight, nickel-iron slag powder is 60-120 parts by weight, slag powder is 50-100 parts by weight, and the rotation speed of the ball mill is 200-300 r / min.

[0011] Furthermore, the silane coupling agent is γ-aminopropyltriethoxysilane.

[0012] Furthermore, the silane emulsion is an isooctyltriethoxysilane emulsion.

[0013] Furthermore, the thixotropic agent is a thermoplastic emulsion or nano-clay.

[0014] Furthermore, in step (2), the D50 particle size of the glass micropowder is 5 to 12 μm.

[0015] Furthermore, in step (2), the ball milling modification is carried out using a horizontal planetary ball mill with a rotation speed of 300-350 r / min and a ball milling time of 60-90 min.

[0016] Further, in step (3), the PP-HDPE blended fiber is melt-blended and extruded into fibers with a PP:HDPE mass ratio of 7:3; the processing conditions of the oxygen plasma treatment machine are: pure oxygen, low temperature plasma power of 300W, and duration of 3 to 5 minutes.

[0017] Furthermore, in step (4), the particle size of the rubber particles is 40 to 80 mesh.

[0018] Further, in step (4), the premixing modification is carried out by first stirring at room temperature for 120 s in a low-speed mixer at a speed of 200 r / min, and then allowing it to stand and be sealed for 30 min to allow the silane coupling agent to be fully adsorbed on the surface of the rubber particles.

[0019] Furthermore, in step (6), the polycarboxylate superplasticizer is a polycarboxylate-based high-performance water-reducing agent.

[0020] Further, in step (7), the dry mixing time is 90-150s, and the stirring time after adding the alkaline activator solution and the functional component mixture is 60-120s; in step (8), the stirring time is 40-80s.

[0021] Further, in step (9), the nozzle diameter of the print head is 15-40 mm, the extrusion pressure is 0.5-1.5 MPa, the extrusion speed is 30-60 mm / s, and the layer height is 8-20 mm.

[0022] Furthermore, in step (9), the curing process involves first maintaining a constant temperature of 25°C for 48 hours, and then uniformly raising the temperature to 45-50°C for heat-activated curing.

[0023] Further, the alkali activator is sodium silicate, with a content of 15 to 35 parts by weight; the thixotropic agent has a content of 0.5 to 1.5 parts by weight; and the polycarboxylate superplasticizer has a content of 8 to 15 parts by weight.

[0024] The present invention also provides template-free hydrophobic concrete obtained by the preparation method described above.

[0025] The present invention has the following advantages: 1. Ultra-low carbon emissions: This invention uses multi-source industrial solid waste such as steel slag, nickel-iron slag, ore slag, and glass powder as the main cementitious materials. The cement replacement rate can reach 100%, the solid waste utilization rate of a single cubic meter of concrete exceeds 70%, and the carbon emissions are reduced by more than 50% compared with traditional C50 concrete.

[0026] 2. Excellent self-waterproofing performance: The alkali-activated system forms a dense pore structure, reducing pore connectivity. Combined with the overall hydrophobic modification of isooctyltriethoxysilane emulsion, the entire cross section of the concrete has low water absorption characteristics, with water absorption rate reduced by more than 90% compared to ordinary cement systems; the impermeability grade reaches P12 or above, the contact angle is ≥120°, and the electrical flux is ≤450C.

[0027] 3. Self-healing ability of cracks: For microcracks smaller than 0.2mm, the healing rate can reach more than 92% after water curing, forming a stable sealing layer, effectively blocking the seepage path, and improving the long-term impermeability and durability of concrete.

[0028] 4. Good 3D printing adaptability: static yield stress 300-500Pa, dynamic yield stress 80-180Pa, interlayer bond strength reaches more than 85% of the overall strength.

[0029] 5. Co-utilization of multi-source solid waste: Simultaneous disposal of various industrial and urban solid wastes such as steel slag, nickel-iron slag, ore slag, waste glass, and waste tires, resulting in significant environmental benefits. Attached Figure Description

[0030] The present invention will be further described below with reference to the accompanying drawings and embodiments.

[0031] Figure 1 This is a site diagram of the concrete 3D printing production of subway wall trenches according to the present invention. Detailed Implementation

[0032] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings and specific embodiments. Unless otherwise specified in the embodiments, conditions are performed according to conventional conditions or conditions recommended by the manufacturer. Raw materials whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0033] The silane coupling agent described in the following examples is γ-aminopropyltriethoxysilane, the cement-based penetrating crystalline concrete waterproofing agent is DST-B concrete self-healing waterproofing agent, and the silane emulsion is isooctyltriethoxysilane emulsion.

[0034] Example 1 (All Solid Waste) A method for preparing formwork-free hydrophobic concrete includes the following steps: (1) Composite activation of solid waste micro powder. 120 parts by weight of steel slag micro powder, 90 parts by weight of nickel-iron slag micro powder and 80 parts by weight of slag micro powder were mixed and ground in a ball mill to make the specific surface area of ​​the mixed micro powder not less than 400 m² / kg. 0.5 parts by weight of silane coupling agent were added and stirred evenly for surface modification. 55 parts by weight of glass micro powder were premixed with 3 parts by weight of silane emulsion and ball milled for modification.

[0035] (2) Functional component pretreatment. 1.5 parts by weight of PP-HDPE blended fiber were placed in an oxygen plasma treatment machine for 4 minutes; 25 parts by weight of rubber granules were premixed with the remaining 0.5 parts by weight of silane coupling agent for modification.

[0036] (3) Preparation of alkali activating solution and microemulsion. Dissolve 25 parts by weight of sodium silicate in 60 parts by weight of water, stir until completely dissolved, and let stand and cool to room temperature to obtain alkali activator solution; ultrasonically emulsify and disperse the remaining 100 parts by weight of water, 4 parts by weight of silane emulsion and 12 parts by weight of polycarboxylic acid-based high-performance water-reducing agent to obtain functional component mixture.

[0037] (4) Special mixing. Dry mix 1100 parts by weight of graded crushed stone, 700 parts by weight of recycled quartz sand, activated solid waste powder, modified glass powder, and 1.0 part by weight of warm wheel rubber for 120 seconds; add alkali activator solution and functional component mixture, and stir at low speed for 90 seconds; evenly sprinkle in plasma-treated PP-HDPE blended fiber, modified rubber particles and 20 parts by weight of cement-based penetrating crystallizing waterproofing agent, and stir at high speed for 60 seconds; finely adjust the slump to 65 mm and the spread to 400 mm.

[0038] (5) Template-free extrusion molding construction. The concrete mixture is transported to the printing head by a screw pump with a nozzle diameter of 25mm and an extrusion pressure of 1.0MPa. The path is planned based on the BIM model, with a layer height of 15mm and an extrusion speed of 45mm / s. After extrusion molding, the concrete is covered with a film and cured at a constant temperature of 25℃ for 48h, and then the temperature is raised to 48℃ for heat-activated curing.

[0039] The performance of the formwork-free hydrophobic concrete prepared in this embodiment was tested, and the results are shown in Table 1. The 28-day compressive strength was 52.3 MPa, the impermeability grade reached P12, the contact angle was 122°, the electrical flux was 380C, the initial setting time was 28 min, the interlayer bond strength was 2.1 MPa, and the carbon emissions were reduced by 82% compared with traditional C50 concrete.

[0040] Example 2 (Ultra-low Cement) A method for preparing formwork-free hydrophobic concrete includes the following steps: (1) Solid waste micro powder composite activation. 100 parts by weight of steel slag micro powder, 70 parts by weight of nickel-iron slag micro powder and 60 parts by weight of slag micro powder were mixed and ground in a ball mill to make the specific surface area of ​​the mixed micro powder not less than 400 m² / kg. 0.5 parts by weight of silane coupling agent were added and stirred evenly for surface modification. 55 parts by weight of glass micro powder were premixed with 3 parts by weight of silane emulsion and ball milled for modification.

[0041] (2) Functional component pretreatment. 2.0 parts by weight of PP-HDPE blended fiber were placed in an oxygen plasma treatment machine for 4 minutes; 25 parts by weight of rubber granules were premixed and modified with the remaining 0.5 parts by weight of silane coupling agent.

[0042] (3) Preparation of alkali activating solution and microemulsion. Dissolve 18 parts by weight of sodium silicate in 50 parts by weight of water, stir until completely dissolved, and let stand and cool to room temperature to obtain alkali activator solution; ultrasonically emulsify and disperse the remaining 110 parts by weight of water, 4 parts by weight of silane emulsion and 12 parts by weight of polycarboxylic acid-based high-performance water-reducing agent to obtain functional component mixture.

[0043] (4) Special mixing. Dry mix 1100 parts by weight of graded crushed stone, 700 parts by weight of recycled quartz sand, activated solid waste micro powder, modified glass micro powder, and 1.0 parts by weight of nano clay for 120 seconds; add alkali activator solution and functional component mixture, and stir at low speed for 90 seconds; evenly sprinkle in plasma-treated PP-HDPE blended fiber, modified rubber particles and 20 parts by weight of cement-based penetrating crystallizing waterproofing agent, and stir at high speed for 60 seconds; finely adjust the slump to 60 mm and the spread to 380 mm.

[0044] (5) Template-free extrusion molding construction. The concrete mixture is transported to the printing head by a screw pump with a nozzle diameter of 25mm and an extrusion pressure of 1.0MPa. The path is planned based on the BIM model, with a layer height of 15mm and an extrusion speed of 45mm / s. After extrusion molding, the concrete is covered with a film and cured at a constant temperature of 25℃ for 48h, and then the temperature is raised to 48℃ for heat-activated curing.

[0045] The performance of the formwork-free hydrophobic concrete prepared in this embodiment was tested, and the results are shown in Table 1. The 28-day compressive strength was 58.6 MPa, the impermeability grade reached P14, the contact angle was 124°, the electrical flux was 350C, the initial setting time was 22 min, the interlayer bond strength was 2.4 MPa, and the carbon emissions were reduced by 68% compared with traditional C50 concrete.

[0046] Example 3 (Extremely Low Shrinkage) A method for preparing formwork-free hydrophobic concrete includes the following steps: (1) Composite activation of solid waste micro powder. 120 parts by weight of steel slag micro powder, 90 parts by weight of nickel-iron slag micro powder and 80 parts by weight of slag micro powder were mixed and ground in a ball mill to make the specific surface area of ​​the mixed micro powder not less than 400 m² / kg. 0.5 parts by weight of silane coupling agent were added and stirred evenly for surface modification. 65 parts by weight of glass micro powder were premixed with 3 parts by weight of silane emulsion and ball milled for modification.

[0047] (2) Functional component pretreatment. 2.2 parts by weight of PP-HDPE blended fiber were placed in an oxygen plasma treatment machine for 4 minutes; 35 parts by weight of rubber granules were premixed with the remaining 0.5 parts by weight of silane coupling agent for modification.

[0048] (3) Preparation of alkali activating solution and microemulsion. Dissolve 25 parts by weight of sodium silicate in 60 parts by weight of water, stir until completely dissolved, and let stand and cool to room temperature to obtain alkali activator solution; ultrasonically emulsify and disperse the remaining 100 parts by weight of water, 4 parts by weight of silane emulsion and 12 parts by weight of polycarboxylic acid-based high-performance water-reducing agent to obtain functional component mixture.

[0049] (4) Special mixing. Dry mix 1100 parts by weight of graded crushed stone, 700 parts by weight of recycled quartz sand, activated solid waste micro powder, modified glass micro powder, and 1.0 part by weight of warm wheel rubber for 120 seconds; add alkali activator solution and functional component mixture, and stir at low speed for 90 seconds; evenly sprinkle in plasma-treated PP-HDPE blended fiber, modified rubber particles and 20 parts by weight of cement-based penetrating crystallizing waterproofing agent, and stir at high speed for 60 seconds; finely adjust the slump to 70 mm and the spread to 420 mm.

[0050] (5) Template-free extrusion molding construction. The concrete mixture is transported to the printing head by a screw pump with a nozzle diameter of 25mm and an extrusion pressure of 1.0MPa. The path is planned based on the BIM model, with a layer height of 15mm and an extrusion speed of 45mm / s. After extrusion molding, the concrete is covered with a film and cured at a constant temperature of 25℃ for 48h, and then the temperature is raised to 48℃ for heat-activated curing.

[0051] The performance of the formwork-free hydrophobic concrete prepared in this embodiment was tested, and the results are shown in Table 1. The 28-day compressive strength was 50.8 MPa, the impermeability grade reached P12, the contact angle was 120°, the electrical flux was 410C, the initial setting time was 30 min, the interlayer bond strength was 2.0 MPa, and the carbon emissions were reduced by 83% compared with traditional C50 concrete.

[0052] The performance test results of Examples 1-3 are shown in Table 1.

[0053] Table 1 Performance test results of Examples 1-3

[0054] Comparative Example 1 (without rubber particles) According to the all-solid-waste standard mix of Example 1 (120 parts steel slag, 90 parts nickel-iron slag, 80 parts ore slag, 25 parts alkali activator, 7 parts silane emulsion, 1.5 parts fiber, 20 parts self-healing additive, 1.0 part thixotropic agent, 12 parts superplasticizer, 160 parts water), only rubber particles were removed, and the remaining components remained unchanged. The 28-day compressive strength was 47.1 MPa, the contact angle was 111°, the 0.2 mm crack healing rate was 75%, the drying shrinkage rate was 0.048%, and the interlaminar bond strength was 1.6 MPa.

[0055] The results showed that without the elastic buffer of rubber particles, drying shrinkage increased significantly, microcracks increased, and hydrophobic properties and crack self-healing effect were significantly reduced.

[0056] Comparative Example 2 (without glass micropowder) Based on the all-solid-waste standard formulation of Example 1, only glass micropowder was removed, while the other components remained unchanged. The 28-day compressive strength was 44.6 MPa, the contact angle was 105°, the healing rate was 71%, the drying shrinkage was 0.039%, and the interlaminar bond strength was 1.4 MPa.

[0057] The results show that when the large pores of the matrix are not filled with glass micropowder, the internal water seepage channels increase, the hydrophobicity decreases significantly, and the matrix density is insufficient.

[0058] Comparative Example 3 (Silane coupling agent only) Based on the solid waste standard formulation of Example 1, rubber particles and glass micropowder were removed, retaining only the silane coupling agent. The 28-day compressive strength was 40.2 MPa, the contact angle was 93°, the healing rate was 58%, the drying shrinkage was 0.065%, and the interlayer adhesion was 1.1 MPa.

[0059] The results show that silane coupling agents alone cannot compensate for matrix porosity and shrinkage defects, the hydrophobicity drops to the level of ordinary concrete, and the risk of cracking increases significantly.

[0060] Comparative Example 4 (without silane coupling agent) Based on the solid waste standard formulation of Example 1, only the silane coupling agent was removed, while the rubber particles and glass micropowder were retained. The 28-day compressive strength was 42.8 MPa, the contact angle was 98°, the healing rate was 64%, the drying shrinkage was 0.042%, and the interlayer adhesion was 1.2 MPa.

[0061] The results show that when silane molecular bridges are lacking, the rubber particles, glass powder and cementitious matrix debond at the interface, resulting in a large number of interfacial gaps inside, and the waterproof and mechanical properties decrease simultaneously.

[0062] The results of Comparative Examples 1-4 above confirm that only when silane coupling agent, rubber particles, and glass micropowder are combined can a synergistic system of "interfacial bonding-pore filling-stress buffering" be formed. The absence of any single component or any component will cause a significant reduction in hydrophobicity, crack resistance, and interlayer adhesion performance.

[0063] Comparative Example 5 (without self-healing additive) Based on the all-solid-waste formulation of Example 1, only the cement-based penetrating crystallizing waterproofing agent was removed, while the other components remained completely unchanged. The impermeability grade was reduced to P6, the healing rate of 0.2mm cracks after 28 days was only 27%, the repair depth did not exceed 8mm, and the electrical flux increased to 765C.

[0064] The results show that the self-healing additive is the core functional component of the long-lasting self-waterproofing of this invention. Without it, the material only has surface hydrophobicity and loses the function of actively repairing internal microcracks. The impermeability, self-healing ability and chloride ion resistance are greatly deteriorated, and it cannot meet the long-term waterproofing requirements of underground engineering and tunnel structures.

[0065] While specific embodiments of the present invention have been described above, those skilled in the art should understand that the specific embodiments described are merely illustrative and not intended to limit the scope of the present invention. Equivalent modifications and variations made by those skilled in the art in accordance with the spirit of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing formwork-free hydrophobic concrete, characterized in that, Includes the following steps: (1) After mixing the all-solid waste cementitious system or the low-cement cementitious system, grind it in a ball mill so that the specific surface area of ​​the mixed powder is not less than 400 m² / kg; add some silane coupling agent to the ground mixed powder, stir and mix evenly to perform surface modification; the all-solid waste cementitious system or the low-cement cementitious system includes steel slag powder, nickel iron slag powder and slag powder; (2) After premixing glass micro powder with a portion of silane emulsion, ball milling was performed to modify the glass micro powder. (3) Place the PP-HDPE blended fibers in an oxygen plasma treatment machine for 3 to 5 minutes; (4) The rubber particles are premixed with the remaining silane coupling agent to obtain modified rubber particles; (5) Dissolve the alkali activator in water, stir until completely dissolved, and let stand and cool to room temperature to obtain an alkali activator solution; (6) The remaining water, silane emulsion and polycarboxylate superplasticizer are ultrasonically emulsified and dispersed to obtain a functional component mixture; (7) Dry mix the aggregate, the composite activated micro powder obtained in step (1), the modified glass micro powder obtained in step (2) and the thixotropic agent, and then add the alkali activator solution prepared in step (5) and the functional component mixture obtained in step (6), and stir evenly. (8) Add the PP-HDPE blended fiber treated in step (3), the modified rubber particles obtained in step (4), and the cement-based penetrating crystallizing waterproofing agent evenly to the mixture obtained in step (7), and continue to stir evenly to obtain a formwork-free hydrophobic concrete mixture. (9) The concrete mixture is transported to the print head by a screw pump for extrusion molding; (10) After extrusion molding is completed, cover with film and cure.

2. The preparation method according to claim 1, characterized in that, In step (1), in the all-solid waste cementing system or low-cement cementing system, ordinary silicate cement is 0-80 parts by weight, steel slag powder is 80-150 parts by weight, nickel-iron slag powder is 60-120 parts by weight, slag powder is 50-100 parts by weight, and the rotation speed of the ball mill is 200-300 r / min.

3. The preparation method according to claim 1, characterized in that, In step (2), the D50 particle size of the glass micropowder is 5 to 12 μm.

4. The preparation method according to claim 1, characterized in that, In step (4), the particle size of the rubber particles is 40 to 80 mesh.

5. The preparation method according to claim 1, characterized in that, In step (6), the polycarboxylate superplasticizer is a polycarboxylate-based high-performance water-reducing agent.

6. The preparation method according to claim 1, characterized in that, In step (7), the dry mixing time is 90-150s, and the stirring time after adding the alkaline activator solution and the functional component mixture is 60-120s; in step (8), the stirring time is 40-80s.

7. The preparation method according to claim 1, characterized in that, In step (9), the nozzle diameter of the print head is 15-40 mm, the extrusion pressure is 0.5-1.5 MPa, the extrusion speed is 30-60 mm / s, and the layer height is 8-20 mm.

8. The preparation method according to claim 1, characterized in that, In step (9), the curing process involves first maintaining a constant temperature of 25°C for 48 hours, and then uniformly raising the temperature to 45-50°C for heat-activated curing.

9. The preparation method according to claim 1, characterized in that, The alkali activator is sodium silicate, with a content of 15-35 parts by weight; the thixotropic agent has a content of 0.5-1.5 parts by weight; and the polycarboxylate superplasticizer has a content of 8-15 parts by weight.

10. A formwork-free hydrophobic concrete obtained by the preparation method according to any one of claims 1 to 9.